Decision-making ability limitations and brain neural activity changes in healthcare workers after mild COVID-19 - Yaotian Gao; Keyi Lin; Bangyue Wang; Wei Ji; Jia Liu; Mengcheng Du; Wei Wang; Yan Li; Xiaowen Du; Yuyang Wang; Tao Jiang (Neuroscience Research)
Studies have demonstrated that the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) extensively affects brain function. Although cognitive dysfunction is considered a common manifestation in COVID-19 patients during the recovery period, the potential changes in decision-making ability, are not yet clear. Decision-making functions are essential to the work of healthcare workers. However, there is a lack of a multidimensional assessment of its functioning in COVID-19 cases. Here, we used tests combined with the resting-state functional magnetic resonance imaging (rs-fMRI) stabilization feature amplitude of low-frequency fluctuations (ALFF) to explore decision-making behavior and brain neural activity changes in healthcare workers after mild COVID-19. Participants were divided into the SARS-CoV-2 infected group (SI, n = 41) and healthy controls (HC, n = 42). All participants underwent a series of neuropsychological tests. They performed the Iowa Gambling Task (IGT) and the Game of Dice Task (GDT), followed by fMRI (n = 20) to assess their decision-making ability under ambiguous and risky conditions and changes in brain neural activity. The SI group performed worse in verbal memory than the HC group. Furthermore, the SI group performed worse in the IGT, whereas no significant difference was observed in the GDT. In addition, rs-fMRI showed enhanced spontaneous neural activity in the postcentral gyrus and inferior parietal lobe in the SI group compared to the HC group.